Influence of some structural characteristics of ionic liquids on homogeneous and heterogeneous characteristics of their mixtures with organic substances - S. A. Reshetov; A. K. Frolkova (Тонкие химические технологии, 2010)
This article presents a study on degree of influence of formalized structural characteristics of ionic liquids, such as length of alkyl radical of cation, degree of cation's symmetry, type of cation, type of anion and some others, on homogeneous and heterogeneous characteristics of mixtures of ionic liquids with organic substances.